Complex space source theory of spatially localized electromagnetic waves - Seshadri, S. R. 1925- (SciTech Publishing, 2014)
The book has fifteen (15) chapters that deal with the following topics: fundamental Gaussian beam; fundamental Gaussian wave; origin of point current source in complex space; basic full Gaussian wave; complex source point theory; extended full Gaussian wave; cylindrically symmetric transverse magnetic full Gaussian wave; two higher-order full Gaussian waves; basic full complex-argument Laguerre-Gauss wave; basic full real-argument Laguerre-Gauss wave; basic full complex-argument Hermite-Gauss wave; basic full real-argument Hermite-Gauss wave; basic full modified Bessel-Gauss wave; partially coherent and partially incoherent full Gaussian wave; and Airy beams and waves. Appendices on Green's function for the Helmholtz equation, An integral, Green's function for the paraxial equation, electromagnetic fields, and Airy integral are given.